Parents' Attitudes Toward Mathematics and the Influence on Their Students' Attitudes toward Mathematics: A Quantitative Study. (May 2017) - Mohr‐Schroeder, Margaret J.; Jackson, Christa; Cavalcanti, Maureen; Jong, Cindy; Craig Schroeder, D.; Speler, Lydia G.
Abstract : The purpose of this study was to investigate parents' attitudes toward mathematics, their students' attitude toward mathematics, and the influence of the parents' attitude on the students' attitude toward mathematics. Data analyses revealed statistically significant positive correlations between parents' and students' attitudes toward mathematics. Additionally, parents' mathematics attitude significantly predicted students' attitudes toward mathematics (n=146). By understanding the influence of parents' attitudes on students' attitudes toward mathematics, school efforts can be geared toward fostering favorable attitudes toward mathematics among parents.